Content and Quality of Websites for Patients With Chronic Kidney Disease: An Environmental Scan. Issue 1 (July 2019) - Smekal, Michelle; Gil, Sarah; Donald, Maoliosa; Beanlands, Heather; Straus, Sharon; Herrington, Gwen; Sparkes, Dwight; Harwood, Lori; Tong, Allison; Grill, Allan; Tu, Karen; Waldvogel, Blair; et al.
Background: Although numerous websites for patients with chronic kidney disease (CKD) are available, little is known about their content and quality. Objective: To evaluate the quality of CKD websites, and the degree to which they align with information needs identified by patients with CKD. Methods: We identified websites by entering "chronic kidney disease" in 3 search engines:Google.com (with regional variants for Australia, Canada, the United Kingdom, and the United States), Bing.com, and Yahoo.com. We included the first 50 unique English-language sites from each search. We evaluated website content using a 30-point scale comprising 8 priority content domains identified by patients with CKD ( understanding CKD, diet, symptoms, medications, mental/physical health, finances, travel, and work/school ). We used standardized tools to evaluate usability, reliability, and readability (DISCERN, HONcode, LIDA, Reading Ease, and Reading Grade Level). Two reviewers independently conducted the search, screen, and evaluation. Results: Of the 2093 websites identified, 115 were included. Overall, sites covered a mean (SD) of 29% (17.8) of the CKD content areas. The proportion of sites covering content related to understanding CKD, symptoms, and diet was highest (97%, 80%, and 72%, respectively). The proportion of sites covering travel, finances, and work/school content was lowest (22%, 12%, and 12%, respectively). The mean (SD) scores for DISCERN, LIDA and HONcode were 68% (14.6), 71% (14.4), and 75% (17.2), respectively, considered above average for usability and reliability. The mean (SD) Reading Grade Level was 10.6 (2.8) and Reading Ease was 49.8 (14.4), suggesting poor readability. Conclusions: Although many CKD web sites were of reasonable quality, their readability was poor. Furthermore, most sites covered less than 30% of the content patients identified as important for CKD self-management. These results will inform content gaps in internet-accessible information on CKD self-management that should be addressed by future eHealth web-based tools.